MSME Business Transformation in the Digital Era: Digital Innovation as a Driver of Inclusive Business Models in Indonesia (Universitas Terbuka, 2025)
The digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia represents a crucial driver of economic growth and innovation in the country's evolving business landscape. This research examines the role of new technologies in promoting inclusive practices by Indonesian MSMEs, with an emphasis on their current adoption, the difficulties they face, and the opportunities ahead. Using a combination of systematic literature review, case study analysis, and an examination of current policy efforts, this study looks at the present situation of digital transformation among Indonesian MSMEs and discovers what helps them develop inclusive business models. The study shows that while adopting digital technology helps MSMEs expand their market, work more efficiently, and make better profits, these small businesses have to handle substantial challenges, such as limited resources, not having the technical skills required, and insufficient infrastructure. It is explained that with government help, working with other types of businesses and sharing resources, MSMEs are able to use technology to become more competitive and encourage inclusive growth. This study contributes to understanding the intersection of digital innovation and inclusive business models in the context of Indonesia's economic development priorities.